PERCERAIAN KELUARGA PEGAWAI NEGERI SIPIL (PNS) (STUDI KASUS KECAMATAN BANGKO KABUPATEN ROKAN HILIR PROVINSI RIAU) - Lestari, Kartika; Jalil, Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Divorce phenomenon that occurs at this time has become a common thing in society. In fact, these days we often hear a lot of divorce cases are committed by someone who is educated, one among Civil Servants who do divorce. Civil Servants are the elements of the State Apparatus, public servants and society servants should be a good example for the community in the behavior, actions and obedience to the laws and regulations that apply to be able to carry out its obligations. Therefore, the Civil Service shall provide a good example for his subordinates and be an example as a good citizen in the community, including in organizing the family life. The purpose of this study was to find out what are the factors that lead to divorce in the family of Civil Servants and how the aftermath of divorce on families Civil Servants to a family function. The method used to analyze qualitative descriptive with data retrieval technique is by observation and interview. Based on research into the causes of divorce Civil Servants because of domestic violence, infidelity and meddling parents. While the impact of the divorce affect the course of the process of family functioning is mainly a function of socialization, the economic function, the function of protection and affective functions.Keywords: Civil Servants, Divorce, Social Exchange